2013
DOI: 10.11609/jott.o3342.4994-5001
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of medium and large sized mammals in a Cerrado fragment of central Brazil

Abstract: Diversity of mammals in Cerrado FragmentCampos et al.Image 7. Cerdocyon thous (Linnaeus, 1766).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Studies conducted in different countries revealed that the medium and large‐sized mammals recorded were higher than the result obtained from the present study. Some of the studies among others include, Alves, Junior, and Brites (), Njoroge et al (), Cortés‐Marcial, Ayón, and Briones‐Sala (), Brncic, Amarasekaran, McKenna, Mundry, and Kuhl (), Andrade Melo, Gadelha, Silva, Silva Júnior, and Pontes (), Campos, Lage, and Ribeiro (), Oliveira and Hannibal (), and Botelho et al () which recorded 18, 23, 18, 35, 33, 23, 22, and 27, respectively. Alves et al () recorded 18 in a fragment of Cerrado in the Triângulo Mineiro region, southeastern Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in different countries revealed that the medium and large‐sized mammals recorded were higher than the result obtained from the present study. Some of the studies among others include, Alves, Junior, and Brites (), Njoroge et al (), Cortés‐Marcial, Ayón, and Briones‐Sala (), Brncic, Amarasekaran, McKenna, Mundry, and Kuhl (), Andrade Melo, Gadelha, Silva, Silva Júnior, and Pontes (), Campos, Lage, and Ribeiro (), Oliveira and Hannibal (), and Botelho et al () which recorded 18, 23, 18, 35, 33, 23, 22, and 27, respectively. Alves et al () recorded 18 in a fragment of Cerrado in the Triângulo Mineiro region, southeastern Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…However, their study was conducted throughout Sierra Leone to make inferences about species persistence and counted 35 large mammal species. Andrade Melo et al () recorded 33 mammal species; Campos et al () recorded 23 species mammals in Brazil; Oliveira and Hannibal () recorded 22 species in fragmented, semi‐deciduous forest of Brazil and Botelho et al () recorded 27 species of large to medium‐sized mammals in Humaitá Forest Reserve, southwestern Amazonia, and State of Acre, Brazil. These variations might account for variations in climatic condition, census effort spent, variation in vegetation physiognomies, and other environmental characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect evidence is very useful when surveying animals such as carnivores that are naturally rare, elusive, found at low densities and difficult to capture repeatedly. So the presence of medium and large mammals were also been precisely indicated using indirect evidences, using sounds, spines, burrows and faecal droppings (Campos et al, 2013;Borges et al, 2014;Dereje et al, 2015). The collected data were tabulated and analyzed with appropriate statistical methods.…”
Section: Methodsmentioning
confidence: 99%
“…This study showed a similar species richness compared to other inventories in the Cerrado and the presence of endangered species (i.e., nine species) is also noteworthy. In Goiás, other studies with medium and large sized mammals had previously recorded 23 species from the Silvânia National Forest (Campos et al, 2013) and 28 species in Emas National Park (Silveira et al, 2003), both in protected areas.…”
Section: Discussionmentioning
confidence: 99%